Phages in Food Industry Biocontrol and Bioremediation - Cristobal-Cueto, Pablo; García-Quintanilla, Alberto; Esteban, Jaime; García-Quintanilla, Meritxell (Antibiotics (Basel), 2021)
Bacteriophages are ubiquitous in nature and their use is a current promising alternative in biological control. Multidrug resistant (MDR) bacterial strains are present in the livestock industry and phages are attractive candidates to eliminate them and their biofilms. This alternative therapy also reduces the non-desirable effects produced by chemicals on food. The World Health Organization (WHO) estimates that around 420,000 people die due to a foodborne illness annually, suggesting that an improvement in food biocontrol is desirable. This review summarizes relevant studies of phage use in biocontrol focusing on treatments in live animals, plants, surfaces, foods, wastewaters and bioremediation.